PENYULUHAN STRATEGI PEMASARAN BERAS ORGANIK DI DESA LAMEDAI KECAMATAN TANGGETADA KABUPATEN KOLAKA - Doddy Ismunandar Bahari; Masitah Masitah; Helviani Helviani; Nursalam Nursalam; Yuli Purbaningsih; Hasbiadi Hasbiadi; Campina Illa Prihantini; Syahri Wahyuni; Dewi Dewi (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Organic rice has good business opportunities to develop as consumers will get health benefits while producers will get better profits through higher selling prices. The marketing strategy that can be implemented in the marketing of organic rice is to use advances in information technology to promote organic rice, inform about the advantages and benefits of organic rice and obtain market information by using social media and other digital media. Apart from setting up a marketing strategy, it is also necessary to analyze internal factors and external factors. The internal marketing factors are the product mix to be marketed, the price mix, the promotion mix and the sales outlet mix. While the external factors that need to be analyzed are economic force, social, cultural, demographic and environmental forces, political, governmental and legal forces, as well as technological forces